Understanding the Key Determinants of Farmer Loyalty in Sugarcane Farming: Insights from Indonesia - Wisnujati, Nugrahini Susantinah; Rahindra, Hendy Arsyad; Sangadji, Suwandi S.; Paiman, Paiman (Universitas Panji Sakti, 2025)
Granulated sugar is a vital ingredient in Indonesia, widely used as a sweetener in various food and beverage applications. To meet increasing domestic demand, the government has targeted sugar self-sufficiency by 2025. The Indonesian Long-Term Development Plan 2020–2024 outlines efforts to enhance sugarcane productivity. This study aims to identify the factors influencing farmer loyalty in sugarcane cultivation in Indonesia. A quantitative approach was employed to examine the relationships between government policy, sugar company policy, farmer behavior, and cooperative member participation (independent variables) and farmer loyalty (dependent variable). The data were analyzed using SmartPLS version 4. The results indicate that government policy and cooperative member participation do not significantly affect farmer loyalty, while farmer behavior and sugar company policy have a significant positive influence. Notably, the policies of sugar companies play a pivotal role in shaping farmers’ commitment to sugarcane cultivation. These findings suggest that strengthening farmer behavior and enhancing company-level policies can improve loyalty. Furthermore, the results imply that government efforts toward sugar self-sufficiency should not only focus on policy formulation but also ensure alignment with farmers' practical needs and support systems. Integrating sugar company strategies with national agricultural policies could enhance the effectiveness of government programs and accelerate the achievement of self-sufficiency targets.